MINAT BERKONTRIBUSI PADA KEPUASAN KERJA PERAWAT - Malawat, Krisna Yetti; Wigiarti, Sri Herni; Nuraeni, Tuti Sri (Journal of Islamic Nursing, 2020)
The Relationship Interest of being A Nurse with Job Satisfaction at “X”. Hospital udul bahasa Inggris. Job satisfaction has a positive impact for nurses in doing their work.The interest is a mental process that creates whether positive or negative feelings to each individual that are associated with satisfaction in work. The purpose of this research is to identify the relations interest of being a nurse and job satisfaction at "X" Hospital. The method of this research is using probability sampling with 167 samples according to inclusion criteria. The instrument that is being used is modification from various literature reviews which will test to validate and the reliability results to get the valid and reliable results.Results: The average age of the nurses in the Inpatient Room of the “X” Hospital are 33 years old, 9.6 years of working, most of them are female with a Diploma Nursing education, had PNS staff status, are married, and worked in the inpatient unit. Conclusion: The Factors that have a relations with job satisfaction are age, work units, years of service, employment status, and the most influential factor towards the job satisfaction that is the interest of being a nurse. Recommendation: Nursing management creates a program to develop interest of being a nurse by striving for a regular rotation schedule, facilitating work safety and comfort by providing a reward system in the form of increased incentives or with praise, also needs to conduct regular job satisfaction evaluations